Tin oxide dopped caco3 coating on paper for flame retardancy and printability properties - URAL, ELİF (My University, 2022)
Valuable papers, such as checks, promissory notes, money or printing papers used in wallpaper laminates, must be resistant to burning. For this reason, different flame retardants are used in papers. However, generally, the flame retardants used negatively affect printability by creating a hydrophobic surface. For this reason, it is thought that the combination of flame retardants with a filler that will positively affect the printability of paper will be more suitable for such printable papers. For this purpose, this work aimed to obtain paper with good printability and delayed ignition properties by using calcium carbonate, which is a good paper filler, and tin oxide, which is a flame retardant.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KAĞIT & AHŞAP; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, PAPER & WOOD; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); General Materials Science; Physical Sciences; flame retardant; paper coating; printability; tin oxide; calcium carbonate; CALCIUM-CARBONATE; ZINC HYDROXYSTANNATE; FLAMMABILITY; flame retardant; paper coating; printability; tin oxide; calcium carbonate